2015
DOI: 10.1186/s11671-015-1049-2
|View full text |Cite
|
Sign up to set email alerts
|

GaAs-Based Superluminescent Light-Emitting Diodes with 290-nm Emission Bandwidth by Using Hybrid Quantum Well/Quantum Dot Structures

Abstract: A high-performance superluminescent light-emitting diode (SLD) based upon a hybrid quantum well (QW)/quantum dot (QD) active element is reported and is assessed with regard to the resolution obtainable in an optical coherence tomography system. We report on the appearance of strong emission from higher order optical transition from the QW in a hybrid QW/QD structure. This additional emission broadening method contributes significantly to obtaining a 3-dB linewidth of 290 nm centered at 1200 nm, with 2.4 mW at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 38 publications
0
10
0
2
Order By: Relevance
“…However, we note that this may be overoptimistic of the achievable resolution as any additional spectral components of the emission spectrum beyond a single Gaussian will result in power to large positive and negative delays within the coherence function. This may result in ghost images or a resolution penalty due to spectral modulation [46]. At low current densities, the axial resolution is almost identical whether the absorber is O/C or S/C (i.e., in the limit of zero photo-voltage applied to the absorber), with an HWHM of ∼ 2.74 μm.…”
Section: Broadband Gan Sledmentioning
confidence: 99%
“…However, we note that this may be overoptimistic of the achievable resolution as any additional spectral components of the emission spectrum beyond a single Gaussian will result in power to large positive and negative delays within the coherence function. This may result in ghost images or a resolution penalty due to spectral modulation [46]. At low current densities, the axial resolution is almost identical whether the absorber is O/C or S/C (i.e., in the limit of zero photo-voltage applied to the absorber), with an HWHM of ∼ 2.74 μm.…”
Section: Broadband Gan Sledmentioning
confidence: 99%
“…It is well-known that SAQDs constructed by the Stranski-Krastanov (S-K) epitaxy growth mode have been studied extensively for making high-performance lasers over the past three decades [10][11][12][13][14]. As carriers in the QDs structures are strongly confined in all three-dimensional space, the thermal distribution in the QD structure is much smaller than that in bulk and QW structures, which allows one to obtain a low threshold current, high wavelength stability under direct modulation, and high temperature insensitivity for a QD laser [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, self-assembled InAs quantum dots (QDs) 5) are ideal broadband optical gain materials. As an ensemble of InAs QDs has an inherent size and In composition distributions, a broadband emission and gain spectra in the NIR regions, typically in the 1.2-1.3-μm range, can be easily obtained [6][7][8][9][10][11][12] . Many studies have demonstrated the development of broadband tunable lasers based on self-assembled InAs QDs [13][14][15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%